Application of Buccal Fat Pad as Adjunct Flap for Lateral Defect Closure in Palatoplasty - Nurwahida, Nurwahida; Christina, Connie; Jonathan, Malvin (Lingkar Studi Bedah Plastik Foundation, 2021)
Summary: Cleft lip and palate are the most widely recognized craniofacial congenital malformation. The buccal fat pad (BFP) can be utilized to close lateral fistulas at the time of palatoplasty due to its rich blood supply and simple accessibility. The aim is to report on the use of BFP as a pedicled flap in cleft palate surgery and to discuss promising results for this reconstructive concept. The case subject was a five-year-old male born with cleft lip and palate; the cleft lip was operated on 4 months old. The patient was operated on using Bardach's two flap palatoplasty techniques, and for the closure of the lateral lining defect, the BFP was used as a pedicled flap. After the surgery, no abnormality was found, including infection, graft loss, palatal fistulas, or cheek depression. All wounds were fully epithelialized. In palatoplasty, BFP is a safe and reliable method with a fast healing benefit.